PENYELESAIAN GANTI RUGI DALAM SEWA MENYEWA RUMAH OLEH PT.GLOBAL INTI KESEMAKMURAN PERKASA CABANG KOTA PEKANBARU - Raisa Tasya Nabila; Evi Deliana; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The house rental agreement between Mr. Rustian Nur and PT. Global Inti Prosperity Perkasa Pekanbaru City Branch in early 2020 did not go well, the party from PT. Global Inti Semakmuran Perkasa Pekanbaru City Branch defaulted on the house rental agreement number 0025/GIKP-1022/PSR/XI/2019 which caused losses suffered by the creditor, the activities carried out by PT. Global Inti Prosperity Perkasa Pekanbaru City Branch is contrary to what has been regulated in the Act. Therefore, the purpose of writing this thesis, namely: First, how is the implementation of the house rental agreement by PT. Global Inti Kemakmuran Perkasa Pekanbaru City Branch, Second, What are the obstacles in the settlement of compensation in the house rental agreement by PT. Global Core Prosperity Perkasa Pekanbaru City Branch.This type of research can be classified in the type of empirical research, because in this research the author directly conducts it by obtaining field data as the main source, such as the results of interviews and observations as well as to analyze the law which is seen as the behavior of people who always interact and relate to social aspects. . The author conducted this research in a rented house, namely on Jl. Banda Aceh/Sakuntala Pekanbaru City. The population and sample of this study were the owners of the rental house, namely Mr. Rustian Nur and Mr. Ester as Personnel of PT. Global Core Prosperity Perkasa Pekanbaru City Branch. Sources of data used are: primary data and secondary data. Data collection techniques in this study were interviews and literature study.Keywords : Compensation-Rent A House-PT. Global Inti Kesemakmuran Perkasa